Intestinal Epithelial AMPK Deficiency Causes Delayed Colonic Epithelial Repair in DSS-Induced Colitis - Séverine Olivier; Hanna Diounou; Camille Pochard; Lisa Frechin; Emilie Durieu; Marc Foretz; Michel Neunlist; Malvyne Rolli-Derkinderen; Benoit Viollet (Cells, 2022)
Dysfunctions in the intestinal barrier, associated with an altered paracellular pathway, are commonly observed in inflammatory bowel disease (IBD). The AMP-activated protein kinase (AMPK), principally known as a cellular energy sensor, has also been shown to play a key role in the stabilization and assembly of tight junctions. Here, we aimed to investigate the contribution of intestinal epithelial AMPK to the initiation, progression and resolution of acute colitis. We also tested the hypothesis that protection mediated by metformin administration on intestinal epithelium damage required AMPK activation. A dextran sodium sulfate (DSS)-induced colitis model was used to assess disease progression in WT and intestinal epithelial cell (IEC)-specific AMPK KO mice. Barrier integrity was analyzed by measuring paracellular permeability following dextran-4kDa gavage and pro-inflammatory cytokines and tight junction protein expression. The deletion of intestinal epithelial AMPK delayed intestinal injury repair after DSS exposure and was associated with a slower re-epithelization of the intestinal mucosa coupled with severe ulceration and inflammation, and altered barrier function. Following intestinal injury, IEC AMPK KO mice displayed a lower goblet cell counts with concomitant decreased Muc2 gene expression, unveiling an impaired restitution of goblet cells and contribution to wound healing process. Metformin administration during the recovery phase attenuated the severity of DSS-induced colitis through improvement in intestinal repair capacity in both WT and IEC AMPK KO mice. Taken together, these findings demonstrate a critical role for IEC-expressed AMPK in regulating mucosal repair and epithelial regenerative capacity following acute colonic injury. Our studies further underscore the therapeutic potential of metformin to support repair of the injured intestinal epithelium, but this effect is conferred independently of intestinal epithelial AMPK.